2007
DOI: 10.32725/jab.2007.012
|View full text |Cite
|
Sign up to set email alerts
|

A new analytical technique in capillary electrophoresis: studying the levels of nucleotides in human breastmilk

Abstract: The effect of nucleotides in the newborn is a determinant in this first stage of life, and their correct level in breastmilk is vital. We have designed a new method for the assay of nucleotides in milk by capillary electrophoresis (CE) after acid hydrolysis. Breastmilk samples were collected from healthy mothers (ages, 25-35 years) of one month lactation, and stored at-20 °C. The duplicated samples were dissociated by acidic hydrolysis (HClO 4) and the CE assay was performed in an uncoated fused-silica capilla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2009
2009
2016
2016

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 15 publications
1
8
0
Order By: Relevance
“…8 Also, in the last few years, their hypnotic action in infants has been demonstrated by the results of applied research with starter milks for infants with sleep problems. 21,30,31 The higher nocturnal levels of the purine nucleotide 5′AMP were consistent with its nature as a sleep inducer as found in earlier studies. [33][34][35] In addition, as a novel result compared to those reported by other workers, 36 we demonstrated the existence of a circadian rhythm for this nucleotide.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…8 Also, in the last few years, their hypnotic action in infants has been demonstrated by the results of applied research with starter milks for infants with sleep problems. 21,30,31 The higher nocturnal levels of the purine nucleotide 5′AMP were consistent with its nature as a sleep inducer as found in earlier studies. [33][34][35] In addition, as a novel result compared to those reported by other workers, 36 we demonstrated the existence of a circadian rhythm for this nucleotide.…”
Section: Discussionsupporting
confidence: 85%
“…20 Although the most extensively validated method for nucleotide assay in human milk is high performance liquid chromatography (HPLC), our research group has demonstrated that capillary electrophoresis (CE) is another perfectly viable technique. 21 Nearly all nucleotide determinations have studied the variations in their concentrations over the months of lactation. The novelty of the present work is the study of the possible circadian rhythms in the nucleotide content of breast-milk by determining the changes that occur during each 24-h period.…”
Section: Sánchez Et Al Human Milk Nucleotides and Sleepmentioning
confidence: 99%
“…The pH at 7.0 and 9.0 had been used for the analysis of the nucleotides (Cubero et al 2007;Zhou et al 2003). Considering that the pK a value of H 3 BO 3 is 9.24 and the running buffer working within 0.5 pH units of its pK a is better for good buffer capacity (Altria 2007), the influence of the running buffer pH higher than 9.0 (9.5, 9.75, and 10.00) was investigated when the concentration of Na 2 B 4 O 7 and HP-β-CD was kept constant (30 and 80 mmol.L −1 ).…”
Section: Optimization Of Ce Conditionsmentioning
confidence: 99%
“…Detection at 200 nm has been used for the analysis of five 5′-mononucleotides in human breast milk (Cubero et al 2007). However, in order to avoid the potential interference from the sample matrix, a UV detector at 254 nm wavelength was used in this work.…”
Section: Optimization Of Ce Conditionsmentioning
confidence: 99%
See 1 more Smart Citation